Study of Storage Losses in Food Corporation of India, Nagpur Area Office for Financial Year 2015-16 - Bora, Rekha (International Journal of Computer Sciences and Engineering, 2025)
The total production in India is around 280 million tonnes of food grains annually, which includes rice, wheat, cereals, pulses, vegetables and other. The quantum of storage loss and other wastage of foodgrains is very much high. India is the second most heavily populated country after China in the world. It is estimated that India will supersede China by 2025 and will become the most populous country in the world. To feed this huge population is a challenging task and the wastage and losses in foodgrains are taking this challenge to another level of difficulty. According to United Nation Development Programme (UNDP), almost 40 percent of the foodgrains production in India is wasted every year. The reasons behind the wastages are lack of scientific storage structures, lack of storage space, in transit losses, wastage by the users and many more. The wastage quantum of food is the loss of food addition to the loss of resources. The amount of loss not only includes the cost of foodgrains loosed but also includes the cost of resources as well as the loss of the opportunity cost. In India, one major body, who deals with the storage of foodgrains, is Food Corporation of India (FCI). FCI procures and stores the foodgrains like wheat and rice on behalf of the Government of India. FCI uses the scientific methods to prevent the losses in storage and make sure that the stored foodgrains remain in the good condition. Based on the advice from Government of India, FCI releases the foodgrains for the welfare schemes like Public Distribution System, Mid Day Meal or for military quota. In this research work, researcher has studied the quantum of storage loss in FCI, Nagpur Area Office for the year 2015-16. The aim of this research work is to compare the actual losses and prescribed losses limits. The data for this study is collected through the secondary data sources